IMPLEMENTASI ADIWIYATA DALAM UPAYA MEWUJUDKAN PENDIDIKAN LINGKUNGAN HIDUP DI SD NAHDLATUL ULAMA JALAN PUKAT NO. 1 KOTA MEDAN - SAID MUZAMBIQ (Jurnal Ilmiah Econosains, 2014)
Abstract This research used a descriptive qualitative approach. The aims are to describe the implementation Adiwiyata, describe a supporting factor, describes inhibiting factors, and provide a description in overcoming obstacles adiwiyata program at NU SD trawl Road No. 1 Medan. The results showed that the policy environment in the school is going well and integrated into each subject's work utilization of waste paper, palastic and aqua bottles to decorate the atmosphere of the school environment. Besides the establishment of cooperation from local government agencies through the socialization of key activities with the approach of the students and educators in order to gain a good knowledge of the environment, so as to create an atmosphere and environmentally friendly school environment cultured. This proved to won your school's national champion. Some of the barriers are still found among others the limited landfill infrastructure, security officers and public participation around the related concepts of environmentally schools, funding issues, and the support of the community and other agencies are still low. Schools have taken steps to overcome obstacles in the form of strategies to be intensified cooperation with various parties, governments and local communities. Keywords: adiwiyata, environment